Ingenious wheat starch/Lepidium perfoliatum seed mucilage hybrid composite films: Synthesis, incorporating nanostructured Dy2Ce2O7 synthesized via an ultrasound-assisted approach and characterization - Sahar Zinatloo-Ajabshir; Alireza Yousefi; Mario Jekle; Fariborz Sharifianjazi (Carbohydrate Polymer Technologies and Applications)
In this study, Dy2Ce2O7 nanostructures were fabricated using an environmentally friendly, ultrasound-assisted method. These nanostructures were then incorporated into a blend of wheat starch (WS) and Lepidium perfoliatum seed mucilage (LPSM), along with sodium montmorillonite (Na-MMT) nanoparticles. The composite films were produced through a casting method, combining these components to enhance the films' structural and functional properties. FTIR results confirmed the chemical interactions between the NPs and the biopolymeric matrix of the nanocomposites. SEM surface morphology and XRD crystallography results indicated that up to a 1 % weight ratio, the dispersion of Dy2Ce2O7 in the nanocomposite matrix was uniform, while at higher percentages, due to nanoparticle aggregation, crystallinity increased. Interestingly, the elongation of nanocomposites containing Dy2Ce2O7 increased, while their tensile strength and elastic modulus decreased. More than 92 % of UV radiation in the 240–360 nm range was absorbed with the inclusion of 1 % wt. Dy2Ce2O7, and the water vapor permeability (WVP) significantly decreased. Among the Dy2Ce2O7-based nanocomposites, TGA results showed that the WS/LPSM/MMT/Dy1 % sample had the highest thermal stability. Overall, based on the results of this study, the WS/LPSM/MMT/Dy1 % sample was introduced as a composite film with suitable physicochemical and mechanical properties for food and pharmaceutical packaging.